FAKTOR YANG BERHUBUNGAN DENGAN PENYEMBUHAN LUKA POST SECTIO CAESAREA DI RSUD SAWERIGADING PALOPO - Ny. Hikma (Voice of Midwifery, 2017)
Sectio Caesaria (SC) is a labor with laparotomy and hysterotomy. Mothers who have had SC surgery, have the same postpartum care needs of mothers who have vaginal delivery. Post surgical care is necessary to prevent the occurrence of complications in the SCThis study aims to determine the factors associated with wound healing post sectio caesarea in RSUD Sawerigading Palopo 2016. The design of this study using analytical survey method with cross sectional study approach. The population in this study were all mothers who have given birth and sampling techniques of mothers who experienced cesarean delivery sectio sampling technique is the mother who experienced is accidental sampling as many as 45 people. Further data were analyzed by chi-square test.Conclusion: There is correlation between knowledge of mother with wound healing in post-cesarean mother in RSUD Sawerigading Palopo year 2017 based on chi square statistic test p value = 0,000 <0,05. There is a relation of mobilization form with wound healing to post-cesarean mother in RSUD Sawerigading Palopo year 2017 based on chi square statistic test p value = 0,003 <0,05.Suggestion: Provide health education on the importance of maintaining personal hygiene after SC surgery to avoid infection of wound surgery. Health education in post mobil mobilized mother can be done routinely in order to accelerate wound healing. Providing health education on wound care for post-cesarean mother. Health education about the importance of nutritional fulfillment to accelerate wound healing process with high-calorie high-protein diet.Keywords : Wound Healing, Sectio Caesaria, Knowledge, Early Mobilization